CURRICULUM AND SPECIAL EDUCATION IN THE INCLUSIVE PERSPECTIVE: A LOOK AT THE TOCANTINS EDUCATION SYSTEM (Interdisciplinary Studies Journal, 2024)
The objective of the following article is to present reflections on Special Education in the inclusive perspective in the Tocantins Curriculum Document (DCT) and in the Common National Curriculum Base (ENCC). Education for students with disabilities over the years has moved from the care and medical field to the educational field. This is a process that has been built gradually and contemplated by Brazilian educational legislation and international frameworks. This work addresses general aspects of the method of bibliographic and documentary research, in order to analyze how Special Education in the inclusive perspective is being treated in the DCT, which was prepared following the guidelines of the BNCC, which deals with the Statute of the Person with Disabilities (LBI). After examining the data, it is evident that the BNCC treats Special Education from an inclusive perspective, in a fragile way, which also occurs in the DOT. The reflection invites readers to deepen research on the current educational scenario and to consider the instabilities and transformations associated with the perspectives of inclusion, considering crucial issues for its effectiveness.
Keywords: Inclusive Education; BNCC; DCT; LBI; Inclusion